Antimicrobials in Food 2020
DOI: 10.1201/9780429058196-20
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Delivery Systems

Abstract: There is increasing interest in the production of delivery systems to encapsulate natural antimicrobial compounds to increase their antimicrobial efficiency, and also to reduce their interactions with food components and inactivation in the food matrix. Such interest in use of natural antimicrobials in foods is a result of consumer preference for clean-label products, which places demands upon the food industry to replace traditional synthetic preservatives with natural alternatives. In this chapter, different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 120 publications
(156 reference statements)
0
4
0
Order By: Relevance
“…Studies have found that solid lipid nanoparticles loaded with retinoic acid and lauric acid inhibited the growth of Staphylococcus epidermidis , P. acnes, and S. aureus [ 75 ]. A second generation of lipid nanoparticles that can improve the loading capacity and inhibit the excretion of bioactive compounds, called nanostructured lipid carriers, was recently developed from a mixture of solid lipids and liquid lipids [ 76 , 77 , 78 , 79 , 80 ]. Compared to the crystalline lipid core of solid lipid nanoparticles, the structural imperfections of nanostructured lipid carriers with less ordered crystalline arrangement can further improve the loading capacity and prevent the drug leakage for better antibacterial activity.…”
Section: Organic Nanomaterialsmentioning
confidence: 99%
“…Studies have found that solid lipid nanoparticles loaded with retinoic acid and lauric acid inhibited the growth of Staphylococcus epidermidis , P. acnes, and S. aureus [ 75 ]. A second generation of lipid nanoparticles that can improve the loading capacity and inhibit the excretion of bioactive compounds, called nanostructured lipid carriers, was recently developed from a mixture of solid lipids and liquid lipids [ 76 , 77 , 78 , 79 , 80 ]. Compared to the crystalline lipid core of solid lipid nanoparticles, the structural imperfections of nanostructured lipid carriers with less ordered crystalline arrangement can further improve the loading capacity and prevent the drug leakage for better antibacterial activity.…”
Section: Organic Nanomaterialsmentioning
confidence: 99%
“…Liposomes are closed vesicles composed of amphiphilic lipids that can entrap both hydrophobic and hydrophilic molecules [8]. Nanoemulsions are often classified as either oil-in-water (O/W) or water-in-oil (W/O) dispersions stabilized by a surfactant molecule or interfacial film, whose droplet size ranges from 20 to 600 nm [11]. On the other hand, lipid nanoparticles are classified into two categories: (i) SLNs produced from a single solid lipid species and (ii) NLCs formed from blends of liquid lipids (unsaturated fatty acids) and solid lipids [33].…”
Section: Lipid-based Nanostructuresmentioning
confidence: 99%
“…Lipid-based systems have demonstrated significant value as drug delivery platforms in biomedical applications. These delivery systems range from simple oil solutions to complex combinations of lipids, surfactants and co-surfactants [10,11]. Liposomes and solid lipid nanoparticles (SLNs) are two important lipid-based nanostructures widely studied as antimicrobial carriers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation